Production Response of Mung Bean (Vigna radiata L.) on the Application of Phosphorus Fertilizer and Oil Palm Bunch Ash - Faizan Muhammad Nasution; Yaya Hasanah; Mariati Mariati (Talenta Publisher, 2020)
Mung bean need phosphate in seed formation and accelerate pod maturity. In acidic soil the P element is difficult to be available because it is bound by metal metals in the soil, it is given a palm bunch ash containing a lot of organic nutrients to release P from the metal and also increase soil pH. The study aims to determine the effect of P fertilization and palm bunch ash on the growth and production of mung bean. The study was conducted on community land in Medan Selayang from October to December 2019. The study used a factorial randomized block design, with 2 factors. The first factor is P fertilizer (0; 37.5; 112.5 kg SP-36/ha). The second factor is oil palm bunch ash consisting of 0; 2; 4 t/ha. The variables observed were a number of pods, weight of 100 seeds, weight of seed per plots, weight of seed per plant. The results showed that the application of P the applications of P fertilizer 112.5 kg SP-36/ha tended to produce the highest pod number and seed weight per plot. The applications of oil palm bunch ash 2 t/ha significantly increased seed weight per plant, seed weight per plot and pod number.